Sistem Pembelajaran Terpadu Dalam Penerapan Pembelajaran IPS di SD - Amini Amini; Cindi Nurmalasari; Nabila Rahmadina Marpaung; Putri Nabila Yuhanda; Tira Ayu Syahputri; Tiara Risnanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
In simple terms, the notion of learning is an effort of a person or group in achieving learning objectives that have previously been designed before carrying out learning using strategies, approaches and methods. Learning and teaching are concepts that are related to the teaching and learning process. Social studies learning itself uses several relevant sources and uses learning media as an addition to students' knowledge to understand the material. Social studies learning in elementary schools is expected for students to have knowledge and insight regarding the basic concepts of social sciences and humanities, in addition to having social sensitivity to social problems around their environment. Integrated learning applied in elementary schools will help students to have skills in solving social problems through understanding the basic concepts of Social Sciences. Social studies learning is presented with theme-based learning, in one book there are several learning themes related to social studies learning. These themes are related to everyday life, but there are social studies learning values ​​contained in the learning themes. Keywords: Integrated Learning, IPS, SD